Proceedings From the Society for Advancement of Blood Management Annual Meeting 2017: Management Dilemmas of the Surgical Patient—When Blood Is Not an Option. (January 2019) - Tan, Gee Mei; Guinn, Nicole R.; Frank, Steven M.; Shander, Aryeh
Abstract : Vigilance is essential in the perioperative period. When blood is not an option for the patient, especially in a procedure/surgery that normally holds a risk for blood transfusion, complexity is added to the management. Current technology and knowledge has made avoidance of blood transfusion a realistic option but it does require a concerted patient-centered effort from the perioperative team. In this article, we provide suggestions for a successful, safe, and bloodless journey for patients. The approaches include preoperative optimization as well as intraoperative and postoperative techniques to reduce blood loss, and also introduces current innovative substitutes for transfusions. This article also assists in considering and maneuvering through the legal and ethical systems to respect patients' beliefs and ensuring their safety.